2011
DOI: 10.1002/ir.405
|View full text |Cite
|
Sign up to set email alerts
|

Gender matters: An examination of differential effects of the college experience on degree attainment in STEM

Abstract: Although more women than men are enrolled in college within the United States, women remain underrepresented in critical areas of study such as science, technology, engineering, and mathematics (STEM). This is particularly concerning given that STEM fi elds of study are vital to the economic growth and workforce development within the United States (Commission on Professionals in Science and Technology, 2006; National Science Board, 2006). In order for the United States to maintain its status as a competitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 5 publications
2
31
1
1
Order By: Relevance
“…Previous studies (e.g., Gayles & Ampaw, 2011;Sadler et al, 2012;Seymour & Hewitt, 1997;Shapiro & Sax, 2011;Tyson, Lee, Borman, & Hanson, 2007;Wang, 2013) demonstrated that taking more STEM courses, especially those at higher levels, in high school is positively associated with STEM degree completion. The positive and negative experiences that occur in those STEM courses may also play a crucial role in encouraging individuals to persist in STEM or to change their major (Cleaves, 2005;Seymour, 1995;Shapiro & Sax, 2011;Wyer, 2003).…”
Section: Differences In the Nature And Timing Of Triggering Experiencesmentioning
confidence: 95%
“…Previous studies (e.g., Gayles & Ampaw, 2011;Sadler et al, 2012;Seymour & Hewitt, 1997;Shapiro & Sax, 2011;Tyson, Lee, Borman, & Hanson, 2007;Wang, 2013) demonstrated that taking more STEM courses, especially those at higher levels, in high school is positively associated with STEM degree completion. The positive and negative experiences that occur in those STEM courses may also play a crucial role in encouraging individuals to persist in STEM or to change their major (Cleaves, 2005;Seymour, 1995;Shapiro & Sax, 2011;Wyer, 2003).…”
Section: Differences In the Nature And Timing Of Triggering Experiencesmentioning
confidence: 95%
“…Teachers are reported to have varying types of influence, both positive and negative, on students’ academic and career choices. For women, in particular, the results are mixed with evidence of some teachers hindering interest development and others enhancing interest, both in and outside of the classroom (Gayles & Ampaw, ; Hall et al., ; Rask, ; Seymour & Hewitt, ; Shapiro & Sax, ). Women who look up to their teachers as role models or mentors are more likely to maintain their interest in STEM (Gayles & Ampaw, ; Shapiro & Sax, ; Rask, ), whereas women who encounter teachers who exclude them from science activities are likely to become turned off to science (Shapiro & Sax, ; Seymour & Hewitt, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For women, in particular, the results are mixed with evidence of some teachers hindering interest development and others enhancing interest, both in and outside of the classroom (Gayles & Ampaw, ; Hall et al., ; Rask, ; Seymour & Hewitt, ; Shapiro & Sax, ). Women who look up to their teachers as role models or mentors are more likely to maintain their interest in STEM (Gayles & Ampaw, ; Shapiro & Sax, ; Rask, ), whereas women who encounter teachers who exclude them from science activities are likely to become turned off to science (Shapiro & Sax, ; Seymour & Hewitt, ). However, teachers are frequently reported to have a positive effect on men's decisions to major in STEM, as teachers generally portray positive mannerisms toward males taking STEM courses (Maltese & Tai, ; Wyer, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Donnell and Cunningham (2015) recommend interactive engagement with students during class, psychological interventions, tutoring programs within the university or department, and a nation-wide online tutoring program to ensure women in STEM have the support they need to succeed. Retention efforts should also include encouraging faculty attitudes and support (Blair et al 2017, 14-43;Gayles and Ampaw 2011;Santiago 2012), the presence of more women faculty in the department, and undergraduate research experiences (Vieyra, Gilmore, and Timmerman 2011;Wilker 2017). Tutoring can also play a large role in retention, and Robinson (2007) found that firstyear women were more likely to achieve a mid-level or high-level mathematics-oriented major if they regularly made use of mathematics tutoring.…”
Section: Retentionmentioning
confidence: 99%